Technology adoption for the Philippine Health Information Exchange (PHIE) - Serrano, Paul John M. (University of the Philippines Diliman, 2014)
Currently, information systems of health institutions like hospitals, clinics and pharmacies in the country are disconnected from each other that there is virtually no sharing of health records of patients for safer, timely, efficient and effective diagnosis and treatment. Because of this, tests and record keeping are unnecessarily duplicated when a patient visits a different health facility. The challenge is integration and harmonization of data within and across these health institutions and exposing these to external consumers and other stakeholders. To provide an integrated and interoperable environment for the access and retrieval of clinical data, and eventually for sharing of health records across health information systems, the government laid out plans to create the Philippine Health Information Exchange or PHIE that will provide the necessary electronic mobility of clinical information across disparate health care information systems through standardized data formats, message structures, messaging protocols, and patient identification. With this information exchange, there is an assurance that the context of clinical information being exchanged is preserved across health information systems. This paper presents the current status of the health information systems in the country, analyze and assess their readiness for PHIE. It also discusses the proposed technical architecture of PHIE and its components such as the registries, interoperability layer, master data management, data analytics and standardization. Then, it evaluates and assess similar technologies that are applicable to use and benchmark for the implementation of the PHIE. Finally, this paper proposes a technology adoption framework for PHIE based on assessment and evaluation of technological solutions being implemented in other countries. It suggests some guidelines on project governance, capacity building, project implementation, data privacy, service oriented architecture, open standards and systems integration and interoperability that can provide great impact on PHIE implementation.